Complements and coregularity of Fano varieties - Fernando Figueroa; Stefano Filipazzi; Joaquín Moraga; Junyao Peng (Forum of Mathematics, Sigma)
We study the relation between the coregularity, the index of log Calabi–Yau pairs and the complements of Fano varieties. We show that the index of a log Calabi–Yau pair